(untitled) (SCIENCE TIME JOURNAL, 2026)
This paper explores the importance of inclusive education in Uzbekistan through both theoretical perspectives and practical classroom experience. It focuses on the emotional, behavioral and developmental differences among young learners and examines how teachers can support children with diverse learning needs. Based on the author’s experience at Westminster International School in Tashkent (WIST), the article highlights strategies for promoting emotional safety, empathy and adaptive instruction. The findings suggest that inclusive education is not merely about physical access to schooling but about emotional inclusion, individualized attention and teacher preparedness.